Loss of desmoplakin isoform I causes early onset cardiomyopathy and heart failure in a Naxos-like syndrome. Issue 2 (7th February 2006) - Uzumcu, A; Norgett, E E; Dindar, A; Uyguner, O; Nisli, K; Kayserili, H; Sahin, S E; Dupont, E; Severs, N J; Leigh, I M; Yuksel-Apak, M; Kelsell, D P; et al.
Abstract : Background: Desmosomes are cellular junctions important for intercellular adhesion and anchoring the intermediate filament (IF) cytoskeleton to the cell membrane. Desmoplakin (DSP) is the most abundant desmosomal protein with 2 isoforms produced by alternative splicing. Methods: We describe a patient with a recessively inherited arrhythmogenic dilated cardiomyopathy with left and right ventricular involvement, epidermolytic palmoplantar keratoderma, and woolly hair. The patient showed a severe heart phenotype with an early onset and rapid progression to heart failure at 4 years of age. Results: A homozygous nonsense mutation, R1267X, was found in exon 23 of the desmoplakin gene, which results in an isoform specific truncation of the larger DSPI isoform. The loss of most of the DSPI specific rod domain and C-terminal area was confirmed by Western blotting and immunofluorescence. We further showed that the truncated DSPI transcript is unstable, leading to a loss of DSPI. DSPI is reported to be an obligate constituent of desmosomes and the only isoform present in cardiac tissue. To address this, we reviewed the expression of DSP isoforms in the heart. Our data suggest that DSPI is the major cardiac isoform but we also show that specific compartments of the heart have detectable DSPII expression. Conclusions: This is the first description of a phenotype caused by a mutation affecting only one DSP isoform. Our findings emphasise the importance of desmoplakin and desmosomes in epidermal and cardiac function and additionally highlight the possibility that the different isoforms of desmoplakin may have distinct functional properties within the desmosome.